Association of depression and anxiety with cognitive impairment 6 months after stroke - Williams, OA; Demeyere, N (American Academy of Neurology, 2021)
OBJECTIVE: Investigate the associations between general cognitive impairment and domain specific cognitive impairment with post-stroke depression and anxiety at six-months post-stroke.